Promoting Pleasure through Reading through ICT: Bibliographic Review of Initiatives for Students in the School Stage in Latin America (Educación y Tecnología, 2018)
Reading is one of the main learning tools used by students. However, this ability should not only be used as a learning tool in schools, but should also form part of leisure activity. Various studies have proven that pupils who read for pleasure perform better not only academically but also in their personal and professional life.For that reason, in this research we are presenting bibliographic revision of various initiatives that were promoting reading for pleasure among school students in Spanish speaking countries. Analysis is focused on what, when, where and how things have been approached to create reading a pleasant experience.
Keywords: Reading for pleasure; information and communication technology (ICT); promotion reader; educational contexts